2018
DOI: 10.1177/0892705718807955
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermal property of ultrahigh molecular weight polyethylene composites filled by calcium carbonate modified with long chain

Abstract: Ultrahigh molecular weight polyethylene (UHMWPE) is an excellent property polymer, but its poor processability due to high melt viscosity limits the more wide-ranging application. To improve the processability of UHMWPE composites filled by calcium carbonate (CaCO3), a novel method is reported to modify CaCO3. PE wax coated on the surface of CaCO3 (PEW@CaCO3) can be prepared by acrylic acid–modified CaCO3 (AA-CaCO3) and PE wax. The crystallization and melting behavior of UHMWPE and its composites filled by CaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It can also be seen the crystallization enthalpy of PEW-g-CaCO 3 /UHMWPE is higher than that of AA-CaCO 3 /UHMWPE, CaCO 3 / UHMWPE and UHMWPE at cooling rate of 5°C min -1 . In our previous work [36], it is found that the oligomer-modified CaCO 3 can improve the processability of UHMWPE. It is suggested that the presence of oligomer in the surface of PEW-g-CaCO 3 is benefit to the mobility of molecular chain of UHMWPE to increase the degree of crystallization.…”
Section: Resultsmentioning
confidence: 93%
“…It can also be seen the crystallization enthalpy of PEW-g-CaCO 3 /UHMWPE is higher than that of AA-CaCO 3 /UHMWPE, CaCO 3 / UHMWPE and UHMWPE at cooling rate of 5°C min -1 . In our previous work [36], it is found that the oligomer-modified CaCO 3 can improve the processability of UHMWPE. It is suggested that the presence of oligomer in the surface of PEW-g-CaCO 3 is benefit to the mobility of molecular chain of UHMWPE to increase the degree of crystallization.…”
Section: Resultsmentioning
confidence: 93%
“…The CaCO 3 is a known to behave as a nucleating agent and increases the crystallinity of the polymer matrix. 32 cm −1 , CH 2 wagging at 1320-1159 cm −1 , asymmetrical -C-O-C-stretching, symmetrical -C-O-C-stretching at 800-975 cm −1 , CH 2 scissoring at 1453-1459 cm −1 , C-O stretching at 1065-1030 cm −1 and C-C stretching at 979-980 cm −1 , respectively. 33 Calcite and vaterite exhibit main characteristic peaks as 712 cm -1 and 745 cm -1 , respectively.…”
Section: Xrd and Ftir Analysis Of The Compositesmentioning
confidence: 97%
“…15 The mechanical properties of the composites are closely related to their macroscopic defect morphology, the particle size distribution of the filler, and the contact state of the microscopic interfaces between the fillers. [30][31][32][33] The results show that the thermoplastics filled with CaCO 3 with different particle size distributions have lower melting crystallization temperature and lower melting viscosity than the composites filled with a single particle size, which improves the machining and mechanical properties of the composites significantly. 22,[34][35][36] In a study of mica as filler-reinforced polypropylene, Busigin et al 37 noted that the modulus of the composite was related to the aspect ratio of the mica, and the strength was influenced the most by the size or scale diameter of the mica.…”
Section: Introductionmentioning
confidence: 97%